2018
DOI: 10.1093/nar/gky634
|View full text |Cite
|
Sign up to set email alerts
|

Inherited disorders of cobalamin metabolism disrupt nucleocytoplasmic transport of mRNA through impaired methylation/phosphorylation of ELAVL1/HuR

Abstract: The molecular mechanisms that underlie the neurological manifestations of patients with inherited diseases of vitamin B12 (cobalamin) metabolism remain to date obscure. We observed transcriptomic changes of genes involved in RNA metabolism and endoplasmic reticulum stress in a neuronal cell model with impaired cobalamin metabolism. These changes were related to the subcellular mislocalization of several RNA binding proteins, including the ELAVL1/HuR protein implicated in neuronal stress, in this cell model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…This protein is linked to Parkinson's disease [72]. Disruption of ELAVL1/HuR nuclear export is consistent with the effects of inborn errors of vitamin B12 (cobalamin) metabolisms on brain development, neuroplasticity and myelin formation [73].…”
Section: Resultssupporting
confidence: 56%
“…This protein is linked to Parkinson's disease [72]. Disruption of ELAVL1/HuR nuclear export is consistent with the effects of inborn errors of vitamin B12 (cobalamin) metabolisms on brain development, neuroplasticity and myelin formation [73].…”
Section: Resultssupporting
confidence: 56%
“…Research on other diseases suggests that the localization of HuR is of major importance for the function of this RBP. In studies on cobalamin metabolism disorders, the nucleocytoplasmic transport of HuR was shown to be disrupted as a result of dephosphorylation and hypomethylation of HuR, leading to decreased expression of genes involved in the cellular stress response, cell cycle regulation, neurogenesis, and neuroplasticity [35]. In a zebrafish model, changed phosphorylation of HuR led to the disruption of translocation and thereby to less stable gata1 mRNA and impaired formation of red blood cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of Sirt1 against oxidative stress is linked to the deacetylation of check point kinase 2, which increases cell death under oxidative stress [ 79 ]. We and others have shown a link between Sirt1 and RNA binding proteins like HUR in response to cellular stress [ 80 , 81 ]. Mitochondrion is one of the main organelle involved in ROS production [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decreased expression of Sirt1 plays a prominent role in the pathomechanisms of fetal programming produced by MDD in rats (vitamin B12 and folate) [ 19 , 81 , 93 , 94 ]. Vitamin B12 is metabolized into two active cofactors, methyl-cobalamin (Me-Cbl) and adenosyl-cobalamin (Ado-Cbl), the cofactors for cytoplasmic methionine synthase (MS/MTR) and mitochondrial methyl malonyl CoA mutase, respectively [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation